1986
DOI: 10.1128/aem.51.1.217-219.1986
|View full text |Cite
|
Sign up to set email alerts
|

Occurrence of free and conjugated 12,13-epoxytrichothecenes and zearalenone in banana fruits infected with Fusarium moniliforme

Abstract: Three recognized 12,13-epoxytrichothecene mycotoxins, trichothecolone, diacetoxyscirpenol, and T-2 toxin, and a hyperestrogenic factor, zearalenone, together with the fatty acid esters of trichothecolone, scirpenetriol, T-2 tetraol, and zearalenone, were isolated from the flask culture extractives of Fusarium moniliforme Sheldon (IMI 225232) as well as from the fruit of banana (Musa sapientum L.) infected with the same fungus in the field and in storage. The total concentrations of these toxins in the naturall… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
16
0

Year Published

1990
1990
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(16 citation statements)
references
References 6 publications
(12 reference statements)
0
16
0
Order By: Relevance
“…Chakrabarthy and Ghosal (6) concluded that they clearly demonstrated that banana naturally infected with F. moniliforme contained diacetoxyscirpenol, T-2, trichothecolone, and zearalenone. In reality, they only presented biological evidence (skin test and uterotropic response) in their paper, and the chemical study reported was on the culture filtrate.…”
Section: Discussionmentioning
confidence: 99%
“…Chakrabarthy and Ghosal (6) concluded that they clearly demonstrated that banana naturally infected with F. moniliforme contained diacetoxyscirpenol, T-2, trichothecolone, and zearalenone. In reality, they only presented biological evidence (skin test and uterotropic response) in their paper, and the chemical study reported was on the culture filtrate.…”
Section: Discussionmentioning
confidence: 99%
“…A possible explanation could be the presence of either unknown estrogenic U. S. Copyright Clearance Center Code Statement: 0931 -1793/90/3703 -0236$02.50/0 compounds or zearalenone conjugates in the sample material. Previous reports demonstrate the ability of fungi of the genus Fusarium to produce conjugates by themselves (CHAKRABARTI and GHOSAL, 1986;GORST-ALLMAN et al, 1985) or describe the bioconversion of mycotoxins to conjugated compounds by other fungi (KAMIMURA, 1986;EL-SHARKAWY and ABUL-HAIJ, 1987) and cell cultures of plants (ZILL, 1988).…”
Section: Introductionmentioning
confidence: 99%
“…moniliforme isolates have been found to produce three 12,13-epoxytrichothecene mycotoxins (trichothecolone, diacetoxyscirpenol (DAS), and T-2 toxin), the palmitoyl esters of trichothecolone, scirpenetriol, and T-2 tetraol (T-2 TOL), and free and palmitic acid conjugate zearalenone (ZON), all in laboratory cultures. These toxins have also been detected in Musa sapientum L. (a banana variety) infected with this species (8). In many cases, the fruits exhibited no apparent visible signs of fungal contamination.…”
mentioning
confidence: 92%
“…For this purpose, the ability to produce metabolites toxic to Artemia salina L. larvae was assessed and the mycotoxins produced by the different isolates were identified and quantified. With the exception of F. moniliforme (8), this is the first reported study of mycotoxin production by Fusarium species that contaminate bananas from the inside and the outside.…”
mentioning
confidence: 92%